(untitled) (Texas Journal of Philology, Culture and History, 2024)
Neologisms, or newly coined terms and expressions, have long played an important role in the formation of language and communication in various fields. In advertising, neologisms are often used as a powerful tool to attract attention, convey novelty, and evoke specific emotions in the target audience. By introducing new words or reworking existing ones, advertisers strive to create memorable messages, distinguish their products from competitors, and reflect cultural interests. This article focuses on the function of neologisms in advertising texts, as well as the function of “trending” words, how they can increase brand reputation, strengthen emotional connections and facilitate consumer engagement.